EVALUASI KEAMANAN INFORMASI PADA SMA ISLAM AL-AZHAR (SMAIA) 4 KEMANG PRATAMA BERDASARKAN INDEKS KEAMANAN INFORMASI (KAMI) SNI ISO/IEC 27001:2009 - Dedi Saputra; Oryza Gilang (Universitas Bina Sarana Informatika, 2016)
The existence of the technology in a system information becomes very important due to being able to support the process of work and business processes be optimized. SMAIA 4 Kemang Pratama is a formal private education institutions. Increasing management of information technology (IT) in school activities, demanded the holding of information technology audit, which focused on the security of the system, to assess whether the General control and security of information systems able to meet the goal. To find the measure of the level of completeness and maturity of the 5 areas that have been adapted to international standards, i.e. ISO 27001:2005 this research uses Information Security Index (us). The results suggested that Al-Azhar Islamic SENIOR HIGH SCHOOL 4th Kemang Pratama has High category in the role and TIK interests namely of 29 of a total of 48 overall assessment and results of the fifth area is done of the overall total of 588 381 fall into the category needs improvement. There is improvement strategy on information security governance area is adding a special staff, create a regular schedule for staff assessment and audit IT, while the information security technology area that is sikronisasi the whole system that has existed and evaluate and improve system security log recording primarily as security gaps.